Protein Adsorption by Basal Plane Graphite Surfaces: Molecular Images and Nano-Structured Films - A. Orasanu-Gourlay; R.H. Bradley (Adsorption Science & Technology)
The adsorp0tion of human serum albumin (HSA) and human plasma fibronectin (Fn) from solutions in the respective concentration ranges 1–20 μg/ml and 0.1–10 μg/ml by highly orientated pyrolytic graphite (HOPG) surfaces was investigated using atomic force microscopy. Adsorption from solutions of relatively low concentrations (HSA, 1 μg/ml; Fn, 0.1 μg/ml) allowed individual adsorbed protein molecules to be imaged. HSA appeared to take one of two forms (N or F) depending upon the adsorption energy and site, whilst Fn appeared to be adsorbed in the coiled, bent form. AFM analysis of films obtained by adsorption from solutions of higher protein concentrations, which were dried slowly over a, period of 24 h, indicated the formation of network structures with the surface coverage increasing with solution concentration. The precise structure, which was very similar for both proteins, appeared to result from dewetting of the hydrophobic HOPG by the protein solution. A grainy structure resulted when films were dried rapidly. In this case, evaporation occurred before dewetting and protein molecules became isolated in even clusters. The XPS nitrogen 1s signal from adsorbed protein was found to increase as the level of adsorbed protein increased, i.e. as a function of the concentration of the protein solution. Water contact angles decreased from 90° for HOPG to 60° after protein adsorption and then increased slightly to 70° as the level of adsorbed protein increased. Plots of the surface nitrogen concentration (atom %) versus the protein solution concentration were type I in the Brunauer, Deming, Deming and Teller isotherm classification. A linear fit was obtained when these data were plotted in the form of the Langmuir equation which resulted in a monolayer equivalent value of N m = 3.3 atom % protein nitrogen. The main mechanism of adsorption appeared to be dispersion- or hydrophobic-dominated, although electrostatic repulsions between polar surface oxygen groups and the negatively charged HSA may also occur.